The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10750-010-0197-8
|View full text |Cite
|
Sign up to set email alerts
|

Trophic cascade effects of Hoplias malabaricus (Characiformes, Erythrinidae) in subtropical lakes food webs: a mesocosm approach

Abstract: While the cascading effect of piscivorous fish on the pelagic food-web has been well studied in north temperate lakes, little is known about the role of native piscivores in warm lakes. Here, the fish communities are typically characterized by high abundances of small, omnivorous fish exerting a high predation pressure on the zooplankton. We conducted a 1-month replicated mesocosm experiment at subtropical conditions to test the effects of piscivorous (Hoplias malabaricus) fish on phytoplankton biomass and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
6
19
1
1
Order By: Relevance
“…By contrast, in the fish treatments, a cascading effect was revealed by a major reduction of the zooplankton grazing potential and a significant increase in phytoplankton biomass in both climatic zones. Our findings confirm the occurrence of a fish predation-driven structure of zooplankton [2], as suggested also in previous works in subtropical, e.g., [19,26,32,[56][57][58][59][60], temperate, e.g., [61][62][63][64], and even sub-polar systems [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, in the fish treatments, a cascading effect was revealed by a major reduction of the zooplankton grazing potential and a significant increase in phytoplankton biomass in both climatic zones. Our findings confirm the occurrence of a fish predation-driven structure of zooplankton [2], as suggested also in previous works in subtropical, e.g., [19,26,32,[56][57][58][59][60], temperate, e.g., [61][62][63][64], and even sub-polar systems [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…The piscivorous feeding habit of this species in environments of Neotropical regions is well documented in the literature (Corrêa & Piedras, 2008). Experimental studies in the mesocosm have demonstrated that the trahira has an important role in the trophic structuring and regulation of forage species in aquatic environments (Mazzeo et al, 2010). Therefore, this species deserves special attention in studies that seek the conservation of the ichthyofauna in dammed environments, mainly those related to the detritivorous guild, the predominance in the detritus item consumption may be derived of the flooding of a large amount of terrestrial phytomass, which promotes a high production of detritus in reservoirs, as well as depletions in the water level, can favor the growth of grasses and other plants in marginal regions, which with its subsequent submergence, also contribute to detritus production (Agostinho et al, 2007).…”
Section: Acta Limnologicamentioning
confidence: 93%
“…Experimental studies in mesocosms show that H. malabaricus plays an important role in trophic structuring and regulation of forage species in aquatic environments (Mazzeo et al 2010). Therefore, this species deserves special attention to studies aimed at the conservation of the ichthyofauna in dammed environments, especially those considered small and medium sized.…”
Section: Feeding and Trophic Guilds Of Fish In The Brazilian Semiaridmentioning
confidence: 99%